Tyumen District in 1920s: Settlement Numbers and Development Features - A. A. Valitov; V. S. Sulimov (Научный диалог, 2023)
The subject of this study is the rural settlements of the Tyumen district in the first quarter of the 20th century. It is noted that during this period, the Tyumen district was situated at the heart of the Tyumen region, ranking first in terms of population size (44,545 people) and the area of territory covered (5.4 thousand square kilometers). The paper examines changes in the number and typology of settlements within the Tyumen district through the lens of its rural localities. It has been established that the district’s settlement network consisted of 177 localities, falling into 11 types, with villages making up a significant proportion — over 50%. This fact indicates that in long-settled regions, settlement networks have existed in virtually unchanged forms despite various external and internal factors. Fifteen villages were identified as creating the framework of the Tyumen district’s settlement network, demonstrating resilience and successfully adapting to new conditions. For instance, data from 1912 and 1926 show that population numbers in these localities were growing, especially in those settlements occupying advantageous (central) positions within the existing network. Many villages in the Tyumen district attained this status during the Soviet period, even though at the beginning of the 20th century they were mere villages. Successful new connections between settlements were facilitated by transportation factors (the presence of railways, tract roads, and a navigable water artery — the Tura River).